Sensing and Responding of Cardiomyocytes to Changes of Tissue Stiffness in the Diseased Heart - Münch, Juliane; Abdelilah-Seyfried, Salim (Frontiers in Cell and Developmental Biology, 2021)
Cardiomyocytes are permanently exposed to mechanical stimulation due to cardiac contractility. Passive myocardial stiffness is a crucial factor, which defines the physiological ventricular compliance and volume of diastolic filling with blood. Heart diseases often present with increased myocardial stiffness, for instance when fibrotic changes modify the composition of the cardiac extracellular matrix (ECM). Consequently, the ventricle loses its compliance, and the diastolic blood volume is reduced. Recent advances in the field of cardiac mechanobiology revealed that disease-related environmental stiffness changes cause severe alterations in cardiomyocyte cellular behaviour and function. Here, we review the molecular mechanotransduction pathways that enable cardiomyocytes to sense stiffness changes and translate those into an altered gene expression. We will also summarize current knowledge about when myocardial stiffness increases in the diseased heart. Sophisticated in vitro studies revealed functional changes, when cardiomyocytes faced a stiffer matrix. Finally, we will highlight recent studies that described modulations of cardiac stiffness and thus myocardial performance in vivo. Mechanobiology research is just at the cusp of systematic investigations related to mechanical changes in the diseased heart but what is known already makes way for new therapeutic approaches in regenerative biology.